The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/ejss.12562
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter coatings of soil minerals affect adsorptive interactions with phenolic and amino acids

Abstract: Summary Phenolic (PAs) and amino acids (AAs) contribute potentially to the stabilization of organic matter (OM) in soil by forming mineral–organic associations (MOAs). However, little is known about how natural OM coating affects the adsorption of these compounds and their mutual interaction upon adsorption. Therefore, batch adsorption experiments were carried out to study how coatings of minerals with dissolved organic matter (DOM) obtained from forest leaf litter (L‐DOM) and from the O horizon (O‐DOM) affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The mutual interaction among OM classes might be caused by the altered surface properties of MOA induced by adsorbed compounds, and might be also assisted by the flexible nature of adsorbed OM. Gao et al (2017Gao et al ( , 2018. In general, the results indicate an enhanced adsorption of phenolic acids on both pure and OM-coated minerals (values above the 100% lines) after surface conditioning by amino acids (a, c, e).…”
Section: The Role Of Proteinaceous Compounds In Developing Multilayermentioning
confidence: 74%
See 4 more Smart Citations
“…The mutual interaction among OM classes might be caused by the altered surface properties of MOA induced by adsorbed compounds, and might be also assisted by the flexible nature of adsorbed OM. Gao et al (2017Gao et al ( , 2018. In general, the results indicate an enhanced adsorption of phenolic acids on both pure and OM-coated minerals (values above the 100% lines) after surface conditioning by amino acids (a, c, e).…”
Section: The Role Of Proteinaceous Compounds In Developing Multilayermentioning
confidence: 74%
“…Recent batch adsorption studies conducted by our group revealed that conditioning of mineral surfaces by amino acids generally enhanced the adsorption of phenolic acids on both pure and OM-coated minerals (goethite, kaolinite, and montmorillonite; Gao et al, 2017Gao et al, , 2018 Fig. 3).…”
Section: The Role Of Proteinaceous Compounds In Developing Multilayermentioning
confidence: 96%
See 3 more Smart Citations